Widely Electronically Tunable 2, 6‐Disubstituted Dithieno[1, 4]thiazines—Electron‐Rich Fluorophores Up to Intense NIR Emission. Issue 57 (3rd September 2020) - May, Lars; Müller, Thomas J. J.
Abstract: 2, 6‐Difunctionalized dithieno[1, 4]thiazines were efficiently synthesized by (pseudo)five‐ or (pseudo)three‐component one‐pot processes based on lithiation‐electrophilic trapping sequences. As supported by structure–property relationships, the thiophene anellation mode predominantly controls the photophysical and electrochemical properties and the electronic structures (as obtained by DFT calculations). From molecular geometries and redox potentials to fluorescence quantum yields in solution, the interaction of the dithieno[1, 4]thiazine‐core with the substituents causes striking differences within the series of regioisomers. Most interestingly, strong acceptors introduced in anti – anti dithieno[1, 4]thiazines nearly induce a planarization of the ground‐state geometry and a highly intense NIR fluorescence ( ΦF =0.52), whereas an equally substituted syn – syn dithieno[1, 4]thiazine exhibits a much stronger folded molecular structure and fluoresces poorly ( ΦF =0.01). In essence, electrochemical and photophysical properties of dithieno[1, 4]thiazines can be tuned widely and outscore the compared phenothiazine with cathodically shifted oxidation potentials and redshifted and more intense absorption bands. Abstract : Promising donor systems : Four isomeric dithieno[1, 4]thiazines, thieno congeners of phenothiazines, are synthesized by inter‐intra‐molecular Buchwald–Hartwig coupling. Their electronic properties open new avenues as donor systems for molecular electronics.